Pandangan Buruh Gendong di Yogyakarta terhadap Peran Ganda Perempuan - Panani, Sri Yulita Pramulia (Jurnal Filsafat "WISDOM", 2021)
Unskilled female labourer (buruh gendong) is a manifestation of Javanese female workers disrupting the inferiority boundary. They lift heavy goods in the market to help in providing livelihood for their family. This research aimed to analyze how the unskilled female labourers defend their existence as Javanese women who are able to fullfil double burden as the way to provide financial help to their family. This research also analyzed how they view of the women's double roles. This research was a field study using qualitative data collected from detailed interviews, observations, and documentations. Analyzes were done using philosophical approaches, i.e. induction, deduction, comparation, description, and reflection. The results showed that Javanese women were not only refined in character and submissive, but also tough, strong, and decisive in making choice. They viewed the women's double burden as part of their lives which should be ventured with willingess and sincerity. They tackled the conflict arising from the double burden by efficiency in time management and load-sharing in domestic chores. Gender deconstruction was shown as women who also can contribute economically by capitalizing their abilities. Women and men are all in the same level and have the same chances in working side by side with other men. From this research, a new knowledge has been revealed that women's double burden was not always restricting women to contribute to their family. It was depicted by this case in female unskilled labourers in helping their family willingly.